Stabilization of Nrf2 leading to HO-1 activation protects against zinc oxide nanoparticles-induced endothelial cell death - Zhang, Longbin; Zou, Liyong; Jiang, Xuejun; Cheng, Shuqun; Zhang, Jun; Qin, Xia; Qin, Zhexue; Chen, Chengzhi; Zou, Zhen (Nanotoxicology, 2021)
With the abundant production and wide application of zinc oxide nanoparticles (ZnONPs), the potential health risks of ZnONPs have raised serious concerns. Oxidative stress is recognized as the most important outcome of the toxicity induced by ZnONPs. The Nrf2-Keap1 system and its downstream antioxidative genes are the fundamental protective mechanisms for redox hemeostasis. However, the detailed mechanisms of Nrf2 activation in ZnONPs-treated endothelial cells and murine blood vessels have yet to be elucidated. Herein, we show that Nrf2 was activated and played a negative role in cell death induced by ZnONPs. Moreover, we demonstrate that HO-1 was the most extensively upregulated antioxidative gene-activated by Nrf2. Forced overexpression of HO-1, pharmacological activation of HO-1 with the agonists RTA-408 (omaveloxolone, an FDA-approved drug) and RTA-402 repressed cell death, and treatment with HO-1 antagonist SnPP exacerbated the cell death. Importantly, loss of HO-1 diminished the cytoprotective role induced by Nrf2 in ZnONPs-treated HUVEC cells, indicating that the Nrf2-HO-1 axis was the crucial regulatory mechanism for the antioxidative response in the context of ZnONPs-induced endothelial damage. Mechanistically, we demonstrate that the p62-Keap1 axis was not involved in the activation of Nrf2. Intriguingly, the degradation half-life of Nrf2 in HUVEC cells was increased from less than 1 h under quiescent conditions to approximately 6 h under ZnONPs treatment condition; moreover, ZnONPs treatment induced activation of Nrf2/HO-1 and accumulation of ubiquitin in the aorta ventralis of mouse, suggesting that the ubiquitin-proteasome system had been perturbed, which subsequently led to the stabilization of Nrf2 and activation of HO-1. This study might contribute to a better understanding of ZnONPs-associated toxicity.